029 Neurology input for acute medical admissions. Issue 3 (9th February 2012) - Jones, M; Kellett, M; Murphy, C
Abstract : Neurology input into acute medical admissions is highly topical. It is known that neurological cases make up a significant proportion of acute admissions and that such cases are often not managed by neurologists. A recent ABN and RCP report recommends specific commissioning to improve management of acute neurological emergencies. We aimed to establish our current level of input into acute medical admissions and to investigate how further input could be beneficial. We audited all acute medical admissions in 1 month. Stroke and direct referrals to neurology from GPs and A+E were excluded. 1286 admissions were reviewed, 64 patients with neurological presentations were identified (5%). 23 cases were referred to neurology. Same-day discharge was facilitated in seven cases, four were taken to the regional neurology unit. Nine planned, but unnecessary, investigations were cancelled. In 41 cases not referred, neurology input could have potentially saved 47 bed days and 32 unnecessary investigations. Neurology specialist input for acute medical admissions is desirable for a number of reasons: Patients are likely to be diagnosed correctly and discharged more quickly. Complex cases can be transferred to a specialist unit. Unnecessary tests, with their cost and potential harm implications, can be avoided. Our current service relies on the acute medical team referring neurological cases to us. The results suggest care could be improved by proactive, regular neurology input to acute medicine.